1982
DOI: 10.1136/pgmj.58.678.233
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin-induced vasculitis: A dose-related phenomenon in susceptible individuals?

Abstract: Summary A case of warfarin-induced skin vasculitis in a 52-year-old female is reported. Bilateral breast involvement occurred but without progression to necrosis as in previously described cases. The pathogenesis is discussed and prescribing recommendations made in an attempt to avoid the complication in susceptible individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Furosemide may prevent warfarin from binding to plasma proteins (mainly albumin) and therefore increase its availability and anticoagulant effect. A dose-dependency of drug-induced vasculitis has been suggested in some case reports (4). From this point of view, the concomitant use of a medication with a potential drug interaction with warfarin might increase the risk of warfarininduced vasculitis in certain susceptible patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furosemide may prevent warfarin from binding to plasma proteins (mainly albumin) and therefore increase its availability and anticoagulant effect. A dose-dependency of drug-induced vasculitis has been suggested in some case reports (4). From this point of view, the concomitant use of a medication with a potential drug interaction with warfarin might increase the risk of warfarininduced vasculitis in certain susceptible patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ten reports were identified in the English-language literature from the years 1980 to 2011 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). From the reports we collected the following data: patient age at onset, cutaneous manifestations, latency (from initiation of treatment to onset of skin manifestations), treatment strategies for vasculitis, concomitant medications, and outcome.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A comprehensive review of existing literature revealed twenty-three cases of anticoagulant-induced LCV, including two attributed to rivaroxaban use (Table 1), [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. It is worth noting that along with our patient, one of the two reported patients with rivaroxabaninduced LCV was prescribed metformin, another drug rarely implicated as a cause of LCV, prior to the development of symptoms [26,28].…”
Section: Case Discussionmentioning
confidence: 99%
“…Cutaneous necrosis is not a common finding in childhood HSP and has been reported in fewer than 5% of all cases [10]. Pillebout et al determined hemorrhagic necrotic purpura in 35% of adult HSP cases and suggested that the incidence of hemorrhagic necrotic skin lesions increases with age, similarly to renal involvement [2].…”
mentioning
confidence: 99%